Minimal disseminated disease evaluation and outcome in trilateral retinoblastoma - Torbidoni, Ana Vanesa (2018)
Trilateral retinoblastoma (TRb) presents a management challenge, since intracranial tumours are seldom times resectable and quickly disseminate. However, there are no risk factors to predict the final outcome in each patient. Objective To evaluate minimal disseminated disease (MDD) in the bone marrow (BM) and the cerebrospinal fluid (CSF) at diagnosis and during follow-up and reviewing its potential impact in the outcome of patients with TRb. Methods and analysis We evaluated MDD in five patients with TRb, detecting the mRNA of CRX and/or GD2, in samples from BM and CSF, obtained at diagnosis, follow-up and relapse. Results Treatment involved intensive systemic chemotherapy in four patients, one did not receive this treatment and died of progression of the disease. Two patients underwent stem cell rescue. Three patients had leptomeningeal relapse and died. One patient remains disease-free for 84 months. RB1 mutations were identified in the five patients, all of them were null mutations. At diagnosis, one patient had tumour cells in the CSF, and none had the BM involved. Only one case of four presented MDD during follow-up in the CSF, without concomitant detection in the BM. On leptomeningeal relapse, no case had MDD in the BM. In all these cases, cells in the CSF were positive for GD2 and/or CRX. Conclusion CSF dissemination always concluded in the death of the patient, without concomitant systemic dissemination denoting the importance of increasing treatment directed to the CSF compartment. The MDD presence could indicate a forthcoming relapse.